C-reactive Protein-to-albumin Ratio in Spinal Epidural Abscess: Association with Post-treatment Complications. Issue 17 (1st September 2022) - Lindsey, Matthew H.; Xiong, Grace X.; Lightsey, Harry M.; Giberson-Chen, Carew; Goh, Brian; Xu, Raylin Fan; Simpson, Andrew K.; Schoenfeld, Andrew J.
Abstract : Introduction: Spinal epidural abscess (SEA) is a complex medical condition with high morbidity and healthcare costs. Clinical presentation and laboratory data may have prognostic value in forecasting morbidity and mortality. C-reactive protein-to-albumin ratio (CAR) demonstrates promise for the prediction of adverse events in multiple orthopaedic and nonorthopaedic surgical conditions. We investigated the relationship between CAR and outcomes after treatment of SEA. Methods: We retrospectively evaluated adult patients treated within a single healthcare system for a diagnosis of SEA (2005 to 2017). Laboratory and clinical data included age at diagnosis, sex, race, body mass index, smoking status, history of intravenous drug use, Charlson Comorbidity Index, and CAR. The primary outcome was the occurrence of any complication; mortality and readmissions were considered secondarily. We used logistic regression to determine the association between baseline CAR and outcomes, adjusting for confounders. Results: We included 362 patients with a 90-day mortality rate of 13.3% and a 90-day complication rate of 47.8%. A reduced complication rate was observed in the lowest decile of CAR values compared with the remaining 90% of patients, a threshold value of 2.5 (27.0% versus 50.2%; odds ratio [OR] 2.66, 95% confidence interval [CI] 1.22 to 5.81). CAR values in the highest two deciles experienced significantly increased odds of complications compared with the lowest decile (80th: OR 3.44; 95% CI 1.25 to 9.42; 90th: OR 3.28; 95% CI 1.19 to 9.04). Discussion: We found elevated CAR to be associated with an increased likelihood of major morbidity in SEA. We suggest using a CAR value of 2.5 as a threshold for enhanced surveillance and recognizing patients with values above 73.7 as being at exceptional risk of morbidity. Level of Evidence: Level III observational cohort study.